The Heat Treatment Process of Fe-Ni Superalloy for Power Plant Boiler Water Wall Tube Application - Chandrasari, Ayu Zahra; Selly Septianissa (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Many applications across various industrial sectors express the need for the use of superior materials in performance because they generally involve diverse and challenging environmental conditions. These environmental conditions are often characterized by parameters such as extreme temperatures and pressures, significant temperature gradients, high external stresses, the presence of oxidizing and corrosive environmental species, and the presence of abrasive foreign particles. Some components and machines operating at high temperatures, as seen in coal gasification processes, oil processing, gas turbine engines and power generation, steam turbines, as well as metal processing industries, greatly require materials with exceptional performance. The experimental approach begins with the formation of Fe-Ni superalloy samples using a mini DC electric arc furnace. After a series of tests, the samples are then analyzed and characterized using various methods, including optical microscopy, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray Spectroscopy (EDS). The results of this research are expected to provide valuable insights into the consideration of material usage in Steam Power Plants (PLTU) and similar applications.